Micro and Nano Fabrication Tools and Processes - Gatzen, Hans H.; Saile, Volker; Leuthold, Jürg.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
For Microelectromechanical Systems (MEMS) and Nanoelectromechanical Systems (NEMS) production, each product requires a unique process technology. This book provides a comprehensive insight into the tools necessary for fabricating MEMS/NEMS and the process technologies applied. Besides, it describes enabling technologies which are necessary for a successful production, i.e., wafer planarization and bonding, as well as contamination control.
Introduction-MEMS, a Historical Perspective -- Vacuum Technology -- Deposition Technologies -- Etching Technologies -- Doping and Surface Modification -- Lithography -- LIGA -- Nanofabrication by Self-Assembly -- Enabling Technologies I - Wafer Planarization and Bonding -- Enabling Technologies II - Contamination Control -- Device Fabrication - An Example.
Keywords: Nanotechnology; Manufactures; Nanotechnology and Microengineering; Manufacturing, Machines, Tools, Processes; Manufacturing, Machines, Tools, Processes